Examining the association between exposome score for schizophrenia and functioning in schizophrenia, siblings, and healthy controls: Results from the EUGEI study. Issue 1 (19th March 2021) - Erzin, Gamze; Pries, Lotta-Katrin; van Os, Jim; Fusar-Poli, Laura; Delespaul, Philippe; Kenis, Gunter; Luykx, Jurjen J.; Lin, Bochao D.; Richards, Alexander L.; Akdede, Berna; Binbay, Tolga; Altınyazar, Vesile; et al.
Abstract: Background: A cumulative environmental exposure score for schizophrenia (exposome score for schizophrenia [ES-SCZ]) may provide potential utility for risk stratification and outcome prediction. Here, we investigated whether ES-SCZ was associated with functioning in patients with schizophrenia spectrum disorder, unaffected siblings, and healthy controls. Methods: This cross-sectional sample consisted of 1, 261 patients, 1, 282 unaffected siblings, and 1, 525 healthy controls. The Global Assessment of Functioning (GAF) scale was used to assess functioning. ES-SCZ was calculated based on our previously validated method. The association between ES-SCZ and the GAF dimensions (symptom and disability) was analyzed by applying regression models in each group (patients, siblings, and controls). Additional models included polygenic risk score for schizophrenia (PRS-SCZ) as a covariate. Results: ES-SCZ was associated with the GAF dimensions in patients (symptom: B = −1.53, p -value = 0.001; disability: B = −1.44, p -value = 0.001), siblings (symptom: B = −3.07, p -value < 0.001; disability: B = −2.52, p -value < 0.001), and healthy controls (symptom: B = −1.50, p -value < 0.001; disability: B = −1.31, p -value < 0.001). The results remained the same after adjusting for PRS-SCZ. The degree of associations of ES-SCZ with both symptom and disability dimensions were higher in unaffected siblings than in patients and controls. By analyzing an independent dataset (the Genetic Risk and Outcome of Psychosis study), we replicated the results observed in the patient group. Conclusions: Our findings suggest that ES-SCZ shows promise for enhancing risk prediction and stratification in research practice. From a clinical perspective, ES-SCZ may aid in efforts of clinical characterization, operationalizing transdiagnostic clinical staging models, and personalizing clinical management.